Human Capital Basic Approach: Analysis Recruitment, Employee Retention Program, Leadership Development, System Reward, and Talent Management - Juniawan Mandala Putra; Josua Panatap Soehaditama; Agustian Zen; Wenny Desty Febrian; Jumawan (International Journal of Asian Business and Management, 2023)
The purpose of this study is to look at the effectiveness of the human capital department in managing employees to achieve company goals, this study uses a literature review from various national and international journal sources, and the novelty of this study is the formation of a new framework model that previously did not exist, the results of a review of various significant articles. This study does not use respondents or data processing as analysis, this study only concludes previous research for further research. In the future, the variables in this scientific article can be used to advance research using research methods, references, or objects used